P221 Deep dermatophytosis presented as multiple exophytic masses caused by Trichophyton rubrum in immunocompromised patient with rheumatoid arthritis; a case report. (20th September 2022) - Hong, Seong Min; Jang, Seung Hee; Ahn, Sang Woo; Choi, Jong Soo; Shin, Jeong Hwan; Kim, Jayoung; Seol, Jung Eun; Kim, Hyojin
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:    : Dermatophyte invades the stratum corneum and infects the skin, nails, and hair, mostly resulting in superficial infection. Deep dermatophytosis involving dermis and subcutaneous layer was rarely reported in immunocompromised state. Herein, we report a case with deep dermatophytosis caused by Trichophyton (T.) rubrum . A 71-year-old woman presented with multiple erythematous exophytic and subcutaneous nodules located on both lower legs. She was taking immunosuppressive agents for rheumatoid arthritis and had taken antifungal agents for tinea pedis and onychomycosis, which was improperly ceased. Histopathologic examination revealed pseudoepitheliomatous epidermal hyperplasia with microabscess formation in epidermis and diffuse granulomatous inflammation consisting of multinucleated giant cells, lymphocytes, neutrophils, and histiocytes in dermis. Imuunohistochemical staining with periodic acid-schiff (PAS) and Gomori methenamine silver (GMS) showed septate and branched fungal hyphae in dermis. Trichophyton rubrum was identified in fungal culture with tissue and confirmed through phylogenetic analysis of internal transcribed spacer (ITS) and large subunit regions (LSU) in ribosomal RNA. Prior to identification of causative organism, her condition deteriorated into septic shock. Amphotericin B was administered empirically for 6 days in order to prevent hematogenous dissemination and skin lesions were simultaneously resolved. Since deep dermatophytosis appears in various clinical manifestations, it is easy to be mistaken for another disease. If treatment is delayed, immunocompetent patients can progress to severe disease courses like hematogenous dissemination, so clinicians should differentiate this disease and conduct treatment at an appropriate time.